A Voice from the Middle East: Political Content in Arabic Children's Literature - Anati, Nisreen (International Journal of Child, Youth and Family Studies, 2020)
This research paper explores the trends of presenting political and social realities in Arabic children’s literature through a content analysis of 26 award-winning Arabic children’s books published between 2011 and 2018 — after the Arab Spring. The origins of Arabic children’s books are first investigated from a number of different standpoints, and are shown to have traditional, religious, and global ties. I also explore the recent rise of interest in creating Arabic literary works for young children. I deduce that the causes of this increase are a cultural reawakening, globalization, and government support and funding. Finally, the 26 children’s books studied show links between the ethnicity of their authors, their dates of publication, and the illustrations and themes that appear in them. This provides support for the idea that Arabic political reality is often reflected in Arabic children’s literature.